Online Program Management Companies: Friend or Foe of Communication Sciences and Disorders Higher Education? - Peters, Cara; Knight, AnnMarie (Perspectives of the ASHA Special Interest Groups, 2023)
Purpose: Online Program Management companies (OPMs) provide a turn-key solution for higher education institutions that want to build new or move existing programs into an online learning environment. The purposes of this article are to overview the current state of OPM usage by higher education institutions and to identify the benefits and drawbacks of using an OPM. Method: This conceptual viewpoint article is based on a review of the literature and informal interviews with administrators who had previous experience in working with OPMs. Results: The processes and structures of OPMs, including service offerings and contractual arrangements, are explained. Numerous benefits of OPMs were identified, including increased enrollments, speed to market, and marketing expertise, among others. Several drawbacks were highlighted, such as yielding control to the OPM, a lack of transparency, aggressive recruitment practices, and more. Conclusions: The future of OPMs is discussed, especially with respect to the financial and legal implications. Implications for Communication Sciences and Disorder programs are also highlighted.